2011
DOI: 10.1097/mbc.0b013e32834bdb32
|View full text |Cite
|
Sign up to set email alerts
|

Differences in fibrin fiber diameters in healthy individuals and thromboembolic ischemic stroke patients

Abstract: Cerebrovascular disease is one of the leading causes of death and the cause of long-term adult disability. An important characteristic of thromboembolic ischemic stroke is a prothrombotic or hypercoagulable state and altered fibrin clot structure, whereas a resistance to fibrinolysis is also present. An expansive fibrin network is created when adding thrombin, and in stroke, the network appears thickened, netted and matted, compared with that of healthy individuals. Although this is clearly visible in microgra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 16 publications
(22 reference statements)
2
36
0
Order By: Relevance
“…However, we and others have observed that their diameter and morphology changes markedly in a variety of vascular and inflammatory diseases, typically producing 'dense matter deposits' (e.g. (Jörneskog et al, 1996;Dunn and Ariëns, 2004;Dunn et al, 2005;Dunn et al, 2006;Pieters et al, 2006;Alzahrani and Ajjan, 2010;Pretorius et al, 2011a;Pretorius et al, 2011b;Alzahrani et al, 2012;Pretorius and Kell, 2014;Pretorius et al, 2015)).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…However, we and others have observed that their diameter and morphology changes markedly in a variety of vascular and inflammatory diseases, typically producing 'dense matter deposits' (e.g. (Jörneskog et al, 1996;Dunn and Ariëns, 2004;Dunn et al, 2005;Dunn et al, 2006;Pieters et al, 2006;Alzahrani and Ajjan, 2010;Pretorius et al, 2011a;Pretorius et al, 2011b;Alzahrani et al, 2012;Pretorius and Kell, 2014;Pretorius et al, 2015)).…”
Section: Introductionmentioning
confidence: 83%
“…When thrombin is added to the platelet poor plasma (PPP) of healthy controls, the fibres forming the subsequent clot appear like a plate of noodles or spaghetti in the scanning electron microscope (Campbell et al, 2010;Pretorius et al, 2011b;Weigandt et al, 2012;Bester et al, 2015;Kell and Pretorius, 2015b). However, we and others have observed that their diameter and morphology changes markedly in a variety of vascular and inflammatory diseases, typically producing 'dense matter deposits' (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A representative micrograph of each sample was selected, and subsequently a 10x5 grid was superimposed onto the picture. One fiber was randomly selected out of every block of the grid, ensuring that fiber measurements were not duplicated, and that fibers were systematically assessed to prevent observer bias [29,30]. Fibrin fiber thickness was measured with ImageJ (ImageJ is a public domain, Java-based image processing program developed at the National Institutes of Health: http://rsbweb.nih.gov/ij/).…”
Section: Sem-based Analysesmentioning
confidence: 99%
“…2C shows an extensive fibrin network created with added human thrombin. These figures are representative micrographs chosen from our database of hundreds of micrographs let and erythrocyte morphology to be drastically altered in stroke 15,16,[49][50][51][52] , showing thrombo-embolic ischaemic stroke to be a hypercoagulable or prothrombotic condition 16) . This technique provides detailed, high resolution images that can show specific changes to ultrastructure.…”
Section: Sem In Thrombo-embolic Ischaemic Strokementioning
confidence: 99%
“…The formed thrombus can either become embedded in a fibrin network (which forms after tissue factor release has activated the extrinsic coagulation pathway) or break away because of high shear forces, becoming an embolus. Central to the involvement of platelets is an aberrant coagulation pathway physiology, leading to a matted clot consisting of dense fibrin fibers [15][16][17] . Fig.…”
Section: Pathogenesis Of Thrombo-embolic Ischaemic Strokementioning
confidence: 99%